دور تمويل التعليم العالي بالجامعات النيجيرية في تحقيق التنمية المستدامة: The Role of Financing Higher Education in Nigerian Universities in Achieving Sustainable Development - سمير محمد حسن (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تهدف الدراسة الحالية إلى التعرف على دور تمويل التعليم العالي بالجامعات النيجيرية بولاية كانو وتأثيرها على التنمية المستدامة. وتكمن مشكلة الدراسة في تدني تمويل التعليم العالي بالجامعات النيجيرية مما ينعكس سلباً على استدامة التعليم العالي وعلى التنمية المستدامة. وتبرز أهمية الدراسة من خلال تسليط الضوء على أهمية تمويل التعليم العالي بالجامعات النيجيرية ومصادر الحصول على هذا التمويل كأحد أهم العوامل التي يمكن من خلالها استكمال الطلاب لدراستهم. واتبعت الدراسة المنهج النوعي وذلك بغرض الحصول على المزيد من المعلومات الدقيقة حول مصادر تمويل التعليم العالي التقليدية وتأثير ذلك على استدامة التعليم وتحقيق التنمية المستدامة. وبلغ مجتمع الدراسة عدد ثلاثة جامعات نيجيرية وهم جامعة حكومية وفيدرالية وجامعة خاصة للتعرف على تأثير تمويل التعليم العالي بالجامعات النيجيرية على التنمية المستدامة. وبلغت عينة الدراسة حوالي ثلاثة من أصل خمسة من المسؤولين عن تمويل التعليم العالي بالجامعات النيجيرية. وكذلك فإن الدراسة اتبعت المقابلات غير منظمة أو المفتوحه وذلك للحصول على المزيد من المعلومات حول تمويل التعليم العالي وما إذا كانت تصلح فكرة الوقف النقدي من عدمه. ولقد أوضحت نتائج الدراسة أن مصادر تمويل التعليم العالي بالجامعات النيجيرية التقليدية متنوعه منها ما يمكن الحصول عليه من خلال صندوق الهبات والتبرعات التي يمكن القيام بها من خلال المبادرات المجتمعية، كما أوضحت نتائج الدراسة أن فكرة الوقف النقدي تواجه تحديات كبيرة في تطبيقها، فالفكرة معرضه للقبول والرفض وفقاً لطبيعة الجامعة وطبيعة المواد التي تدرس. ولقد أوصت الدراسة بضرورة التوسع في دراسة تأثير تمويل التعليم العالي بالجامعات النيجيرية من خلال توسيع نطاق الدراسة لتشمل الولايات النيجيرية كافة. Abstract The current study aims to identify the role of financing higher education in Nigerian universities in the state of Kano and its impact on sustainable development. The study problem lies in the low funding of higher education in Nigerian universities, which will negatively affect the sustainability of higher education and sustainable development. The importance of the study is highlighted by highlighting the importance of financing higher education in Nigerian universities and the sources of obtaining this funding as one of the most important factors through which students can complete their studies. The study followed the qualitative approach with the aim of obtaining more accurate information about traditional higher education financing sources and its impact on the sustainability of education and achieving sustainable development. The study population reached the number of three Nigerian universities, which are a governmental, federal and private university, to learn about the impact of financing higher education in Nigerian universities on sustainable development. The sample of the study was about three out of five of those responsible for financing higher education in Nigerian universities. Also, the study followed unstructured or open interviews in order to obtain more information about financing higher education and whether or not it is suitable for the idea of a monetary endowment. The results of the study showed that the sources of financing for higher education in traditional Nigerian universities are varied, including what can be obtained through the endowment and donations fund that can be made through community initiatives, and the results of the study also indicated that the idea of a monetary endowment faces great challenges in its application, so the idea is subject to acceptance and rejection. According to the nature of the university and the nature of the subjects taught. The study recommended the necessity of expanding the study of the impact of financing higher education in Nigerian universities by expanding the scope of study to include all Nigerian states.